Survey of genetic diversity of IgG in wild and domestic rabbits. (29th July 2015) - Pinheiro, A.; Almeida, T.; Esteves, P. J.
Summary We sequenced IgG from genomic DNA of 30 wild European rabbits of O. c. algirus and O. c. cuniculus subspecies from three regions and 15 domestic O. c. cuniculus. Genetic diversity was highest within Iberian wild populations. Only two new amino acid polymorphisms were found, both in O. c. algirus.